The study aims to determine the effect of Intellectual Capital, Capital Structure and Institutional Ownership on Financial Performance with Company Size as Moderating in financial sector companies listed on the Indonesia Stock Exchange (BEI) Period 2020-2 - Kusniawati, Heni; Nuryatno Amin, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Pengaruh Intellectual Capital, Struktur Modal, Kepemilikan Institusional Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Pemoderasi